Cognitive Biases and the Link Between Shyness and Social Anxiety in Early Adolescence. (November 2016) - Weeks, Murray; Ooi, Laura L.; Coplan, Robert J.
Shy children display wariness in unfamiliar social situations and often experience feelings of social anxiety. This study explored the potential mediating role of cognitive biases in the link between shyness and social anxiety in early adolescence. In particular, we focused on judgments of the probability and cost of negative social situations (i.e., judgment biases). Six hundred eighty-six early adolescents aged 10 to 14 years (X ¯ = 11.58, SD = 1.13) completed measures of shyness, judgment biases, and social anxiety. Among the results, shyness, judgment biases, and social anxiety were positively interassociated. Shyness and judgment biases significantly predicted social anxiety. Moreover, elevated judgments of both the probability and cost of negative social situations partially mediated the relation between shyness and social anxiety. Results are discussed in terms of the conceptual pathway from shyness to social anxiety, as well as implications for intervention programs.